23. DELAYED EMERGENCE AFTER GENERAL ANESTHESIA IN A PATIENT UNDERGOING THYROID SURGERY: A CASE REPORT (Vietnam Journal of Community Medicine, 2025)
Delayed awakening after anesthesia is a rare condition but can cause anxiety for both doctors and patients’ families, requiring differential diagnosis and timely treatment. We present a case of a 40-year-old female patient who underwent general anesthesia for thyroid surgery. The patient had a healthy medical history and preoperative laboratory tests were within normal limits. The induction and maintenance of anesthesia were uneventful, and the left grand thyroidectomy and lymph node dissection of group 6 went smoothly during 40 minutes. After the surgery, the patient was released from anesthesia normally. There was a prolonged delay in awakening despite no obvious abnormalities in clinical and laboratory tests. After close monitoring and minimal supportive intervention, the patient was fully awake after 2.5 hours, leaving no sequelae. The case emphasizes the need to recognize early delayed awakening after anesthesia, studying medical literature to develop timely monitoring and treatment strategies, which is very necessary in clinical practice.
Keywords: elayed awakening from anesthesia, general anesthesia, thyroid surgery, delayed recovery.